1996
DOI: 10.1038/sc.1996.123
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of patients with spinal cord lesions in the Netherlands: an epidemiological study

Abstract: Very little is known about the occurrence of spinal cord lesions and results of the rehabilitation of patients with such lesions in the Netherlands. This study was conducted to describe the process of rehabilitation in the Dutch situation, to assess the incidence of spinal cord lesions in a regional rehabilitation centre and to characterise differences between traumatic and non-traumatic spinal cord lesions regarding age, level and extent of lesion. In this study 293 patients were included who were admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
6
36
4
Order By: Relevance
“…The male/ female ratio was slightly lower than that described in previous Dutch studies, 3,7 but lies within the range of 2.5:1 to 5.8:1 reported in international studies. 1,10 Mean age in this study was relatively high, but also within the range reported in the literature (31-50 years).…”
Section: Traumatic Scisupporting
confidence: 58%
See 4 more Smart Citations
“…The male/ female ratio was slightly lower than that described in previous Dutch studies, 3,7 but lies within the range of 2.5:1 to 5.8:1 reported in international studies. 1,10 Mean age in this study was relatively high, but also within the range reported in the literature (31-50 years).…”
Section: Traumatic Scisupporting
confidence: 58%
“…Lesions of vascular origin accounted for a smaller proportion in a study from Turkey (8%), 2 but for about a quarter of non-traumatic lesions in other publications. 7,12,13 An inflammatory cause was found in 17.2% of the patients with SCI in our study, compared to 19.5% reported elsewhere. 12 Not all studies described the same categories of aetiologies, making it difficult to draw comparisons between different studies.…”
Section: Traumatic Scicontrasting
confidence: 40%
See 3 more Smart Citations